2019
DOI: 10.3390/nu11122980
|View full text |Cite|
|
Sign up to set email alerts
|

Eating Jet Lag: A Marker of the Variability in Meal Timing and Its Association with Body Mass Index

Abstract: The timing of food intake has been associated with obesity and adverse metabolic outcomes, independently of the amount or content of food intake and activity level. However, the impact of the variability in the timing of food intake between weekends and weekdays on BMI (body mass index) remains unexplored. To address that, we propose to study a marker of the variability of meal timing on weekends versus weekdays (denominated as ‘eating jet lag’) that could be associated with increments in BMI. This cross-secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
113
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(120 citation statements)
references
References 41 publications
6
113
1
Order By: Relevance
“…Later wake times may also increase the likelihood that children and adolescents skip breakfast, which has been associated with increased risk for overweight and obesity in elementary aged children [58] and adolescents [59]. Shifts in meal timing have also recently been identified as an indicator of risk for overweight or obesity [60]. Whatever the mechanism, the finding that children are sleeping later and longer during summer vacation coupled with data indicating that BMI gain accelerates as well suggests that even though children are sleeping more during summer vacation, later sleep timingand any co-existing unhealthy behaviors (e.g., evening snacking), may be overriding the benefits derived from increased sleep duration.…”
Section: Discussionmentioning
confidence: 99%
“…Later wake times may also increase the likelihood that children and adolescents skip breakfast, which has been associated with increased risk for overweight and obesity in elementary aged children [58] and adolescents [59]. Shifts in meal timing have also recently been identified as an indicator of risk for overweight or obesity [60]. Whatever the mechanism, the finding that children are sleeping later and longer during summer vacation coupled with data indicating that BMI gain accelerates as well suggests that even though children are sleeping more during summer vacation, later sleep timingand any co-existing unhealthy behaviors (e.g., evening snacking), may be overriding the benefits derived from increased sleep duration.…”
Section: Discussionmentioning
confidence: 99%
“…Later wake times may also increase the likelihood that children and adolescents skip breakfast, which has been associated with increased risk for overweight and obesity in elementary aged children (55) and adolescents (56). Shifts in meal timing have also recently been identified as an indicator of risk for overweight or obesity (57). Whatever the mechanism, the finding that children are sleeping later and longer during summer vacation coupled with data indicating that BMI gain accelerates as well suggests that even though children are sleeping more during summer vacation, later sleep timing -and any co-existing unhealthy behaviors (e.g., evening snacking), may be overriding the benefits derived from increased sleep duration.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it has been reported that weekly fluctuations in meal timing may be associated with chronotype. In a cross-sectional study on young adults, a higher variation in meal timing during the week was observed in evening-type subjects (33) . A review study suggested that evening-type individuals, defined as those who prefer to perform activities in the evening hours and sleep and wake up late or those who have an eveningness preference, are most likely to have unhealthy dietary habits (45) .…”
Section: Discussionmentioning
confidence: 96%